EXTERNAL AUDIT AS AN INSTRUMENT OF TRANSPARENCY AND ASSURANCE IN FINANCIAL STATEMENTS: A CASE STUDY OF THE COMETA GROUP (Editora Impacto Científico, 2025)
External auditing is an essential tool to strengthen users’ confidence in accounting and financial statements, ensuring transparency and the assurance of information. In this context, this study aimed to understand the impacts of this practice in the corporate environment. The main objective of the research was to analyze how external auditing contributed to the improvement of assurance and transparency in accounting statements in the private sector, using a case study of Grupo Cometa, located in the city of Cáceres-MT. The research sample consisted of the accounting manager of Grupo Cometa, a professional responsible for the preparation and supervision of financial statements. Methodologically, this was a qualitative case study, with a descriptive approach and basic nature, using a questionnaire applied to the accounting manager, who is directly involved in the preparation and supervision of financial statements and in interaction with external auditing. The analysis was conducted based on content analysis techniques. The research results were obtained and presented after the full development of the study, aiming to demonstrate the impacts and benefits of external auditing in strengthening transparency and the assurance of accounting information.DOI: https://doi.org/10.56238/edimpacto2025.090-046